Introduction to IoT with machine learning and image processing using Raspberry Pi - Kulkarni, Shrirang Ambaji; Gurupur, Varadraj P.; Fernandes, Steven L. (Boca Raton : CRC Press, 2020)
Machine Learning a branch of Artificial Intelligence is influencing the society, industry and academia at large. The adaptability of Python programming language to Machine Learning has increased its popularity further. Another technology on the horizon is Internet of Things (IoT). The present book tries to address IoT, Python and Machine Learning along with a small introduction to Image Processing. If you are a novice programmer or have just started exploring IoT or Machine Learning with Python, then this book is for you. Features: Raspberry Pi as IoT is described along with the procedure for installation and configuration. A simple introduction to Python Programming Language along with its popular library packages like NumPy, Pandas, SciPy and Matplotlib are dealt in an exhaustive manner along with relevant examples. Machine Learning along with Python Scikit-Learn library is explained to audience with an emphasis on supervised learning and classification. Image processing on IoT is introduced to the audience who love to apply Machine Learning algorithms to Images The book follows hands-on approach and provide a huge collection of Python programs.
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Authors -- CHAPTER 1 . Introduction -- CHAPTER 2 . Raspberry Pi Unraveled -- CHAPTER 3 . Python and Its Libraries for Machine Learning -- CHAPTER 4 . Machine Learning -- CHAPTER 5 . Introduction to Image Processing -- Bibliography -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things; Machine learning; Raspberry Pi (Computer) -- Programming; Image processing -- Digital techniques -- Computer programs; COMPUTERS / Computer Graphics / Game Programming & Design; COMPUTERS / Database Management / Data Mining; COMPUTERS / Machine Theory